2014
DOI: 10.1007/s12630-014-0190-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of uterotonic agents: in vitro contractions in isolated myometrial strips of labouring and non-labouring women

Abstract: Oxytocin induces superior myometrial contractions compared with ergonovine, PGF2α, and misoprostol. The effect of oxytocin is reduced in myometrium of women with oxytocin-augmented labour; however, it is still superior to the other uterotonics. This trial was registered at ClinicalTrials.gov: NCT01689311.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
0
19
1
4
Order By: Relevance
“…Oxytocin is commonly used as the first line utertonic agent but if the uterus fails to contract adequately current practice guidelines recommend the use of additional utertonic agents to prevent and treat PPH such as ergometrine, misporostol and carboprost [12][13][14] . Availability of pharmacological agents that exert their effects through alternative receptor mechanisms is extremely relevant in light of emergencing evidence of decreased responsiveness to oxytocin in myometrium previously exposed to oxytocin 15,16 . Despite the long standing use of ergometrine, the exact mechanism by which it exerts its uterotonic effect in human tissue has never been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Oxytocin is commonly used as the first line utertonic agent but if the uterus fails to contract adequately current practice guidelines recommend the use of additional utertonic agents to prevent and treat PPH such as ergometrine, misporostol and carboprost [12][13][14] . Availability of pharmacological agents that exert their effects through alternative receptor mechanisms is extremely relevant in light of emergencing evidence of decreased responsiveness to oxytocin in myometrium previously exposed to oxytocin 15,16 . Despite the long standing use of ergometrine, the exact mechanism by which it exerts its uterotonic effect in human tissue has never been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported similar differences in these parameters in previous studies. 14,22 Our results showed reduced oxytocin-induced myometrial contractility when MgSO 4 was present during dose-response testing, but not when present only in the pretreatment period. This implies an extracellular mechanism of action, or at least that any intracellular component has minimal tocolytic impact.…”
Section: Discussionmentioning
confidence: 64%
“…Previous studies have shown that the effect size between any two treatment groups, where a significant difference was apparent in MI, can be expected to be 0.7-1.4 HgÁc/10 min, with a standard error (SE) of 0.25-0.35 HgÁc/10 min. 14,22 Using these assumptions and powering the analysis for a beta of 80% and an alpha of 0.05, the sample size required was calculated as 28 experiments per treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] There is some evidence in the literature suggesting resensitization of OTRs following cessation of oxytocin stimulation in a previously desensitized myometrium; however, this has not been consistently demonstrated in vitro. [14][15][16] Moreover, in the clinical setting, it is unclear if discontinuing oxytocin after labour augmentation will allow for the myometrium to respond effectively to subsequent oxytocin stimulation.…”
Section: Résumémentioning
confidence: 99%